Independent regulation of cyclo-oxygenase 2 expression by p42/44 mitogen-activated protein kinases and Ca2+/calmodulin-dependent kinase. - Goppelt-Struebe, M (1999)
5-Hydroxytryptamine (5-HT, 'serotonin') is a potent inducer of the early response gene cyclo-oxygenase 2 (Cox-2; prostaglandin G/H synthase) in mesangial cells. Protein kinase C (PKC), Ca2+-dependent enzymes and mitogen-activated protein kinase (p42/44 MAPK) have previously been shown to be essential modules of the signalling pathway leading from the pertussis-insensitive 5-HT2A receptor to the induction of Cox-2 mRNA expression. In the present study, PKC activation was linked to the 5-HT-mediated phosphorylation and thus the activation of p42/44 MAPK: the inhibition of PKC by the specific inhibitor GF109203x prevented p42/44 MAPK activation. Ca2+/calmodulin-dependent (CaM) kinase II delta2 was detected in mesangial cells by Western blot analysis. The inhibition of CaM kinase by the inhibitors KN62 or KN93 led to a partial inhibition of 5-HT-induced Cox-2 mRNA expression and decreased basal, but not PMA-mediated, Cox-2 expression. The 5-HT-mediated activation of MAPK was not decreased by KN62 or KN93, excluding CaM kinase as a signalling module upstream of p42/44 MAPK. Taken together, these results indicate a modulatory involvement of CaM kinase in the regulation of 5-HT-mediated Cox-2 mRNA expression in addition to the main pathway that consists of the activation of PKC and p42/44 MAPK.